2021
DOI: 10.1021/acssuschemeng.0c08033
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Long-Term Stability of Hydrotalcite-Derived Catalysts in Hydrogenolysis of Glycerol by Incorporation of Ca(II)

Abstract: Selective hydrogenolysis of biomass-derived glycerol into 1,2-propanediol (1,2-PDO) is of practical importance to upgrade the huge amounts of surplus glycerol derived from renewable biomass. Herewith, we report that hydrotalcite-derived catalysts have been employed for selective hydrogenolysis of glycerol into 1,2-PDO under aqueous phase and base-free conditions. In particular, the catalyst of Co 2 -Ca 4 -Al 3 was recorded as a good catalyst with an optimum glycerol conversion of 100% and 1,2-PDO selectivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…[150] The presence of Co 0 nanoparticles is very important: a hydrotalcite-derived Co 2 -Ca 4 -Al 3 catalyzed several steps for the formation of 1,2-PD. [151] XRD characterization revealed the formation of a CaCO 3 layer on the surface of the catalyst that reduced the number of strong basic sites, enhanced the number of moderate basic sites, and helped to avoid the metals leaching during the reaction, carried out at 483 K and 40 bar H 2 in a continuous-flow fixed-bed reactor. So, the product was obtained with excellent selectivity (91 %) at complete GL conversion.…”
Section: Cobaltmentioning
confidence: 99%
See 1 more Smart Citation
“…[150] The presence of Co 0 nanoparticles is very important: a hydrotalcite-derived Co 2 -Ca 4 -Al 3 catalyzed several steps for the formation of 1,2-PD. [151] XRD characterization revealed the formation of a CaCO 3 layer on the surface of the catalyst that reduced the number of strong basic sites, enhanced the number of moderate basic sites, and helped to avoid the metals leaching during the reaction, carried out at 483 K and 40 bar H 2 in a continuous-flow fixed-bed reactor. So, the product was obtained with excellent selectivity (91 %) at complete GL conversion.…”
Section: Cobaltmentioning
confidence: 99%
“…So, the product was obtained with excellent selectivity (91 %) at complete GL conversion. [151] Cobalt aluminate nanoparticles were also used as catalyst in the gas phase GL transformation. They were prepared by flame spray pyrolysis and employed for the catalytic reaction at 573 K and 1 bar H 2 .…”
Section: Cobaltmentioning
confidence: 99%
“…In general, the hydrogenolysis of glycerol utilizes a homogeneous base (i.e., Ca(OH) 2 , NaOH, and Ba(OH) 2 ) and a supported transition metal catalyst (i.e., Pd, Pt, Ru, Ni, or Cu) to catalyze this process, which can selectively break the C-C and/or C-O bonds. [52][53][54] Gong et al 55 employed hydrotalcite-derived catalysts to selectively hydrolyze glycerol to 1,2-propanediol in aqueous phase and under alkali-free conditions. Their results showed that the Co 2 -Ca 4 -Al 3 catalyst reached 100% optimal glycerol conversion and 90.5% 1,2-propanediol selectivity in glycerol hydrogenolysis.…”
Section: Anaerobic Fermentationmentioning
confidence: 99%
“…into them, which could lead to high catalytic activity and selectivity. 40 However, the LDH-derived catalysts usually appear as aggregated lumps, which have a negative impact on the mass transfer processes and the exposure of active sites in the catalytic reactions. 41,42 Therefore, grafting LDH precursors onto other supports with abundant space through in situ growth strategies could be beneficial for improving their catalytic performance.…”
Section: ■ Introductionmentioning
confidence: 99%